Biomechanics of judo breakfall for osoto-gari in adolescent judokas - Koshida, S.; Ishii, T.; Matsuda, T.; Hashimoto, T. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Regardless of relatively higher head injury occurrence, few studies have investigated the biomechanics of a judo breakfall technique in adolescent judokas. The aim of the present study was to demonstrate biomechanical characteristics of the breakfall technique performed by experienced adolescent judokas during the "osoto-gari" throw by comparing it with those performed by experienced adult and novice adult judokas. Motion data from the breakfall technique were collected with a three-dimensional motion analysis method. No significant differences were observed in the hip and neck movement patterns between the novice and the adolescent judokas (p > 0.05), but not between the experienced adult and adolescent judokas. This suggests that regardless of experience, the breakfall skill level of the adolescent judokas is not similar to that of adult experienced judokas.